New ways to learn geography – challenges of the 21st century - Markuszewska, Iwona; Tanskanen, Minna; Vila Subirós, Josep (Quaestiones Geographicae, 2019)
The aim of the article is to get a closer overview of the non-instructional methods of the teaching-learning process of geography. To achieve this goal, the results of the international project Borderland: Border Landscapes Across Europe(undertaken in 2012 and 2013, within the framework of LLP-Erasmus Programme) was presented. Special attention was paid on the innovative approach to learning methods, namely learning by doing (LBD) that was experienced in a multinational environment during the project’s implementation.